Habitats and biodiversity of decapod crustaceans in the SE Gulf of California, México - Hendrickx, Michel E (1996)
Samples of benthic macro-fauna were obtained in different habitats along and off the coast of Southern Sinaloa, Gulf of California, Mexico, from 1978 to 1991. Qccurrence of species of decapod crnstaceans was registered for six habitats, from the intertidal to depth of 1200 m. A total of 299 species were collected, belonging to 53 farnilies and including 17 species of Penaeoidea, 45 of Caridea, 6 of Thalassinidea, 5 of Palinura, 1 of Astacidea, 63 of Anomura, and 162 of Brachyura. Number of species varied considerably from one habitat to another. Highest biodiversity was observed in the Bay of Mazatlán, with 121 species, followed by the continental shelf and the rocky intertidal (107 species each), the estuarine/coasta1 lagoons (48 species), the upper slope (18 species) and the sandy beaches (9 species). Qne species was found to be strictly insular-terrestrial and two are primarily associated with the flotsam. The results of this survey were compared with distribution data available for decapod crnstaceans fauna from the SE Gulf of California and the Eastern Tropical Pacific zoogeographic region (ETP). The fauna collected represents 82% of the species cited for the area for coastal and shallow subtidal habitats (to ca. 115 m depth) and 57.6% of deep-water (> 200 m) species known to occur in the Gulf of California. Except in two cases, similarity indices (SI) based on number of species common to any pair of habitats were all very low. Continental shelf and the Bay of Mazatlán have 57 species in cornmon (SI = 0.50), while rocky shore habitat and the Bay of Mazatlán share 27 species (SI = 0.24). Comparative studies of decapod crustaceans cornmunities for the ETP are almost lacking alltogether. Available data, however, indicate that biodiversity observed in Southern Sinaloa is so far the highest on record for marine and brackish-water habitats for a given section of this tropical zoogeographic region